0169 Tunnel Vision: How Good Are Final Year Medical Students In Identifying Differential Diagnosis On A Busy Ward Round: A Simulated Ward Round At The University Of Edinburgh. (1st November 2014) - Medjoub, Karima; Crichton, Fiona; Edgar, Simon
Abstract : Background: Ward rounds are a busy and complex environment. Aggressive patients can be either distracting to the participants, and often their behaviour can be attributed to personality traits. However, it is common knowledge amongst medical healthcare professionals that it is potentially a symptom of an organic cause. Therefore, is a complex and stressful environment, with multiple tasks to be performed, how likely is a medical student to identify the potential of a serious illness in an aggressive patient. Methodology: We ran a simulated ward round at the university of Edinburgh involving final year medical students (n = 290). We used five patient scenarios with numerous distractors such as phone calls, being asked to perform other tasks, and requesting investigations, as well as being a part of the ward round. Two of the scenarios used were around one patient with acute pancreatitis and another with sepsis and airway compromise. Both these simulated patients were instructed to be aggressive. We measured the time between the patient expressing symptoms to the time of considering a possible cause of the patient's symptoms, and also the number of prompts from faculty and the patients required to do so. The wards rounds included approximately 3 to 5 students, and each ward round was followed by a reflective debrief. Results: The busy environment in addition to the distractors played a major role in delaying the differential diagnosis, and also the required number of prompts. It was interesting that during the debrief sessions the students immediately suspected the issue if they were in a calm and distractor-free environment. Potential impact: The appropriate understanding and acquisition of non- technical skills are an important factor is diluting distractors and avoid potentially disastrous outcomes. Work around the subject should be continued in the future as part of the undergraduate curriculum. References: Flin, R, O'Connor P, Crichton M. Safety at the Sharp End: A Guide to Non-Technical Skills. Surrey: Ashgate; 2008 Fulde, G, 2011. Managing aggressive and violent patients. Australia Prescriber